Revolutionizing Sustainable Public Transportation: The Go-Bus Mobile App Journey With Design Thinking - Saputro, Rujianto Eko; Faturama, Rafi; Sarmini (Politeknik Ganesha Medan, 2024)
Bus Rapid Transit (BRT) has become a popular solution to address traffic congestion in Indonesia, including in Banyumas Regency. However, the supporting services provided by the BRT system still require improvement. This study focuses on designing the Go-Bus application, by integrating gamification elements to encourage the usage of Trans Banyumas. The Design Thinking method is used, encompassing the empathy, definition, ideation, prototype, and testing stages. This prototype undergoes User Satisfaction Testing and Single Ease Question (SEQ). the average score of 84.84% has been reached from the evaluation of 11 tasks by six respondents. Then, satisfaction score of 6.73 indicates Go-Bus as a user-friendly and satisfying application. This research aims to address challenges in motivating and altering user behavior to utilize public transportation. By incorporating gamification into the UI/UX design of the application, Go-Bus offers a solution that enhances user motivation, satisfaction, and encourages a shift towards public transportation usage